Síntese de meso-tetrafenilporfirinas com substituintes reativos no anel meso-fenil visando a obtenção de derivados porfirínicos catiônicos aquossolúveis - Oles, Margarete de Oliveira (2010)
There is a considerable interest in the synthesis of water soluble porphyrins due to its use as models of biological systems, as drugs and as homogeneous catalysts in aqueous media. Within this context, this work describes the synthesis of meso-tetraphenylporphyrins with reactive groups on the meso-phenyl ring to generate trimethylarylammonium salts derivatives, resulting in cationic porphyrins with hydrophilic character. Thus, it was obtained iodide salts of 4-TMA-TPP 13 by the complete alkylation of 4-DMA-TPP 15 (91% yield), and 4-NH2-TPP 12 using 2,6-lutidine (69% yield). The synthesis of porphyrins 2-NO2-TPP 16, 2-NH2-TPP 17, 4-NO2-TPP 14, 4-NH2-TPP 12 and 4-DMA-TPP 15 were also studied. The methods described in the literature for the synthesis of 2-NO2-TPP 16 and 4-NO2-TPP 14 were optimized, and the yield (40%) of for 2-NO2-TPP 16 was higher than those reported in the literature (5% overall yield). Porphyrins 17 and 12 were obtained by reduction of 16 and 14, respectively, using concentrated hydrochloric acid and tin (II) chloride dihydrate, without requiring an inert atmosphere. The method was improved, thus facilitating the isolation and purification steps. The synthesis of 4-DMA-TPP 15 was performed using both Adler-Longo method (5% yield) and a modification of Adler’s method, using 1:1 mixture of propionic and octanoic acids (7,0% yield). The porphyrins were fully characterized by infrared, UV-Vis and RMN spectroscopies. All the spectral data were consistent with those reported in the literature.